Pengaruh Retaliasi, Emosi Negatif, Dan Komitmen Organisasi Terhadap Kecenderungan Melakukan Whistleblowing - Ulfa Afifah; Arumega Zarefar (Akuntansi & Ekonomika, 2021)
Financial crime is increasingly rampant these days. The fact is financial crimes are often seen directly by internal parties in an organization. It is very important to analyze the intention of an employee to do whistleblowing. The purpose of this study was to examine the effect of retaliation, negative emotions (guilt and shame), and organizational commitment on an individual's intention to whistleblowing. This research was conducted in all branches of PT. Telkomsel in Riau Province. The sampling method used was purposive sampling. The data was collected by sending a questionnaire to 150 employees who work in all branches of PT. Telkomsel in Riau Province, but only 69 questionnaires can be processed. The collected data were analyzed using Partial Least Square (PLS). There are four hypotheses in this study. The results of this study concluded that: retaliation, guilt, shame, and organizational commitment effect on the intention to do whistleblowing.